Too old for technology? Stereotype threat and technology use by older adults. Issue 7 (19th May 2022) - Mariano, João; Marques, Sibila; Ramos, Miguel R.; Gerardo, Filomena; Cunha, Cátia Lage da; Girenko, Andrey; Alexandersson, Jan; Stree, Bernard; Lamanna, Michele; Lorenzatto, Maurizio; Mikkelsen, Louise Pierrel; Bundgård-Jørgensen, Uffe; et al.
ABSTRACT: Older adults are often stereotyped as having less technological ability than younger age groups. As a result, older individuals may avoid using technology due to stereotype threat, the fear of confirming negative stereotypes about their social group. The present research examined the role of stereotype threat within the Technology Acceptance Model (TAM). Across two studies, experiencing stereotype threat in the technological domain was indirectly associated with lower levels of technology use among older adults. This was found for subjective (Study 1) and objective measures (Study 2) of use behaviour, and for technology use in general (Study 1) and computer use in particular (Study 2). In line with the predictions of the Technology Acceptance Model, this relationship was mediated by anxiety, perceived ease of use, perceived usefulness, and behavioural intention. Specifically, stereotype threat was negatively associated with perceived ease of use (Studies 1 and 2) and anxiety mediated this relationship (Study 2). These findings suggest that older adults underuse technology due to the threat of confirming ageist stereotypes targeting their age group. Stereotype threat may thus be an important barrier to technology acceptance and usage in late adulthood.